Different responses to facilitatory rTMS according to BDNF genotype. Issue 7 (July 2015) - Hwang, Jung Min; Kim, Yun-Hee; Yoon, Kyung Jae; Uhm, Kyeong Eun; Chang, Won Hyuk
Highlights High-frequency rTMS significantly induces the facilitation of cortical excitability regardless of brain-derived neurotrophic factor (BDNF) genotype. BDNF genotype influence rTMS-induced plasticity based on the rTMS intensity. Our findings suggest that the individual rTMS strategy will be needed according to the brain-derived neurotrophic factor genotype.